Novel artificial metalloenzymes by in vivo incorporation of metal-binding unnatural amino acids. Issue 1 (15th October 2014) - Drienovská, Ivana; Rioz-Martínez, Ana; Draksharapu, Apparao; Roelfes, Gerard
Abstract : Artificial metalloenzymes for asymmetric catalysis were created by in vivo incorporation of unnatural metal binding amino acids into LmrR. Abstract : Artificial metalloenzymes have emerged as an attractive new approach to enantioselective catalysis. Herein, we introduce a novel strategy for preparation of artificial metalloenzymes utilizing amber stop codon suppression methodology for the in vivo incorporation of metal-binding unnatural amino acids. The resulting artificial metalloenzymes were applied in catalytic asymmetric Friedel–Crafts alkylation reactions and up to 83% ee for the product was achieved.